Effect of Thermal Soak Time Towards Polyimide Based-Carbon Tubular Membrane - Norazlianie, Sazali; Ramli, Junid; Siregar, J. P. (Penerbit Akademia Baru, 2020)
Tubular carbon membrane (TCM) was prepared form BTDA-TDI/MDI (P-84) polyimide (PI) has a main precursor that combines with nanocrystalline cellulose (NCC) through controlled carbonization condition. Consideration of the thermal soaking time through the heating process is needed to maintain the proficiency of resultant TCM’s. Thermal soaking time of 30 minutes, 60 minutes, 90 minutes, and 120 minutes was investigated to study the gas properties of the final TCM’s. In the course of TCM’s separation, single gas permeation experiments of CO2 and N2 are performed to investigate the transport mechanism. The PI / NCC TCM’s developed at 120 min of thermal soak time from this study showed the most impressive CO2/N2 performance, selectivity of 66.32±2.18 respectively.